Dobór typu geowłókniny dla skarpy nachylonej z gruntu zbrojonego = The selection type of geofibres for slope wall with reinforcement ground - Chrzan, Tadeusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper cost reinforcement slope wall of 6 m height and loaded continuous loaded continuous load has been analyzed. With analysis result is that minimum cost of building reinforcement slope wall will be for geofibres with maximum tensile strength.
Keywords: geowłóknina; badania